Notes on the history of Peruvian sociology (1896-1930) - Iziga Núñez, Róger (2017)
The history of Peruvian Sociology (1896-1930), is part of a major research project about a theoretical reconstruction of both evolution and development in Peruvian sociology. The investigation covers the pre-sociological period also known as the sociological background phase of ideas and theories, the development of the university professor or the general sociology teaching phase, the so-called National Sociology phase named later as Peruvian Sociology, and finally the phase of scientific and professional development of sociology. This last period is a greater challenge to investigate making an evaluative and critical stocktaking of its institutional dynamics.